Hubungan Infeksi HIV Pada Ibu hamil dengan Persalinan Prematur di RSD Dr. Soebandi Jember - Muhammad Ali Shodikin; Eva Deswinta Maharani; Yuli Hermansyah (Majalah Kedokteran Andalas, 2022)
Human Immunodeficiency Virus (HIV) infectionin pregnant women was increasing in Indonesia. HIV infection will lead complication risk to the mother and their babies. Objective: This study aims to determine the association of HIV infection in pregnant women and preterm birthat RSD Dr. Soebandi Jember.Method:An analytics descriptive with retrospective approach study was conducted. The subjects were medical records of HIV-positive pregnant women group and HIV-negative pregnant women group at RSD Dr. Soebandi Jember from August 2014 to July 2017. Result:Each of groups had 52 samples. In the HIV-positive pregnant women group, there were 19 preterm and 33 aterm birth, on the other hand, in the HIV-negative pregnant women group, there were 15 preterm and 37 aterm birth. The Chi Square test analysis was obtained p value = 0.403 (OR = 1.42). Conclusion: There was no significant correlation between HIV infection in pregnant women and preterm birth.